The relationship between organizational environment antecedents and performance management in local government: Evidence from Ghana - Juliana Abagsonema Abane; Edward Brenya (Future Business Journal, 2021)
The study aimed to investigate the relationship between organizational environment antecedents and their impact on performance management among local government authorities and to further understand the role of the stakeholder and political support in the performance monitoring and review of local governments. The study used quantitative research design techniques in the data collection phase between May and August 2017 in the Greater Accra Region of Ghana. The sample included 850 middle level and senior managers of the Local Government Service. Multiple regression was used to analyze the data. The results of the findings indicate that there is a strong relationship between two organizational environment variables: "stakeholder participation", political support, and performance management providing a variance of 31.8 percent of the changes in the dependent variable. However, the findings further suggest that stakeholder participation was a better predictor of performance management than political support. Additionally, employees' age, gender, and organizational size were statistically significant in the model fit. This study is one of the first of its kind to link two organizational environment indicators (stakeholder support and political support) and their effect on two performance management dimensions (performance monitoring and evaluation, and performance review). Also, few studies have used the structural contingency theory in explaining the influence of the environment on internal business processes of organizations in the performance management literature.
Keywords: 650; Local government; Organizational environment antecedents; Performance management; Political support; Structural contingency theory